IMPLEMENTASI PROGRAM JAMINAN KESEHATAN MASYARAKAT DI KELURAHAN BIROBULI UTARA KECAMATAN PALU SELATAN KOTA PALU - Mekarini, Ni Wayan (Katalogis, 2018)
This study aims at determining the implementation of regional health insurance program in village Birobuli Utara. This research is a qualitative descriptive research. Type of data are primary data and secondary data. Techniques of data collection are carried out through observation, interviews, documentation, and triangulation. Informants are choosen using snowball sampling sampling technique. Techniques of data analysis used are model of Miles and Huberman, namely data reduction, data presentation, and conclusion. Theory used is the theory of Edward III, consisting of four aspects: communication, resources, diposis and bureaucratic structure. Based on results of the research, the implementation of regional health insurance program policy in village Birobuli Utara has not been implemented effectively. First; communication aspect, which is the substance of the policy, has not been achieved consequently what is actually expected of a policy cannot be realized effectively in the absence of socialization conducted by village officials. Second; aspect of the resources, which is human resources owned, in quality and quantity is sufficient already, so is equipment resources to support regional health insurance program policy. Only financial resources to support regional health insurance program, has not been possessed yet. Third; disposition aspect, which is the implementers, tends to be less responsive to the achievement of policy objectives. According to researcher, such disposition is due to the inadequate financial resources, thus hampering the implementation process and complicates the implementers in performing their duties. Fourth, bureaucratic structure, which is the unavailability of standard operating procedures and maintenance service flow displayed, thus making the people do not understand in detail the procedure of regional health insurance program.